Boas práticas para suportar as dimensões de governança ágil de TI na administração pública federal - Silva, Marianne Batista Diniz da (2017)
Governance of Information Technology and Communication (ICT) is still a challenging factor for organizations, both for the public and private sector. A key feature of ICT governance is to add value to the business, as well as collaborate for the organization's performance through continuous decision-making processes, providing efficient and effective IT management aligned with Corporate Governance. Knowing these characteristics, the public organizations are recognized by the control bodies (Audit Court of the Union - ACU, System of Administration of Information Technology Resources - SISP, Strategy of Digital Governance - EGD), which, through this recognition, contribute to the attention of managers in these organizations. In this case, the adoption and direction of good practices that meet the requirements of the control bodies regarding ICT Governance are necessary. Thus, the objective of this dissertation was to propose good practices of ICT Governance to guide the organizations to improve the maturity index of ICT Governance (iGovTI) in the Federal Public Administration (APF), evaluated by the TCU. In order to perform this analysis, a descriptive study was adopted through bibliographic procedures, survey and, finally, the case study for the validation of the proposed framework. After the analysis of the good practices (ITIL, CMMI, COBIT, COSO and others), the proposal of a framework called PeticGov was developed, with the intention of directing the organizations in which good practice (s) based on its deficit. As a result, the validation of the PeticGov Wizard, which meets the phases proposed by the framework, was obtained. In this way, PeticGovWizard was validated regarding usability, the questionnaire, its orientation and its usefulness to the initial and basic organizations. For the first validation (usability) we obtained 21 responses in a survey and it was observed that some aspects need to be improved (layout, information in the tool). For the validation of the questionnaire we obtained a sample of 46 organizations and it was realized that the data were coherent. With respect to the validation of utility of the PeticGov Wizard in the organizations, answers were obtained from 20 employees of institutions with initial and basic capacity. Thus, it was observed that 100% of the respondents affirm that the idea of the PeticGov Wizard tool with respect to the direction of the isolated practices for implantation in the organizations gain strength before the sectors (IT, Administrative, Human Resources and Financial).